The Influence Of Viral Marketing "Clarification Of Video Viral Shopping Drama" On Instagram Towards Brand Awareness Tokomart Tokopedia - Fitri, Velin Noer; Ali, Dini Salmiyah Fithrah (eProceedings of Management, 2025)
This research was conducted to determine the effect of viral marketing on brand awareness at Tokomart Tokopedia.The purpose of this research is to understand and analyze how viral marketing and brand awareness influence thestrategies that Tokopedia has implemented on social media. This research uses a quantitative method with a descriptiveresearch type. The sample used in this study employed nonprobability sampling with a total of 100 respondents. Thedata analysis techniques and methods used are descriptive analysis and multiple linear regression analysis. Based onthe test results, the viral marketing conducted by Tokopedia through the social media platform Instagram has asignificant impact on Tokomart's brand awareness. This is evidenced by thitung> ttabel (9.535 > 1.985) with asignificance test of 0.000 < 0.05. Based on the results of the partial hypothesis test (t-test), it is stated that the variableof viral marketing has a significant effect on brand awareness at Tokomart Tokopedia. Based on the coefficient ofdetermination, it can be concluded that the viral marketing strategy at Tokomart Tokopedia has an impact of 47.6%on the brand awareness of Tokomart Tokopedia, while the remaining 52.6% is influenced by other factors not includedin this study. The conclusion of this research is that Tokopedia has made efforts to enhance Tokomart's brandawareness effectively through viral marketing strategies; however, there are shortcomings in several aspects that needto be improved in the future. Keywords-viral marketing, brand awareness, e-commerce, Instagram